2014
DOI: 10.1177/000313481408000517
|View full text |Cite
|
Sign up to set email alerts
|

Hair Loss in Females after Sleeve Gastrectomy: Predictive Value of Serum Zinc and Iron Levels

Abstract: A common complication after bariatric surgery is hair loss, which is related to rapid weight reduction, but zinc, iron, and other micronutrient deficiencies can also be involved. Little is studied after laparoscopic sleeve gastrectomy (LSG). A prospective observational study was performed of 42 morbidly obese females undergoing LSG. Incidence of hair loss was monitored. Micronutrients were investigated preoperatively and three, six, and 12 months after surgery. Sixteen patients (41%) reported hair loss in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
4
22
0
2
Order By: Relevance
“…9,16 Among these, hair loss is one of the most commonly reported and is related to rapid weight loss and deficiencies of iron, zinc and other micronutrients. 28 In the present study, the prevalence of hair loss was 59.5%, a rate which is in line with that reported by other researchers (40-60%); however, Goldenshluger et al observed a greater frequency of hair loss in MGB patients compared to those who underwent SG, while the opposite was true in the present study. 29 This may be related to the higher number of SG patients included in the current study and the fact that 55.3% had undergone the surgery between 1-2 years previously, a time when weight loss is commonly rapid in bariatric surgery patients.…”
Section: Discussionsupporting
confidence: 92%
“…9,16 Among these, hair loss is one of the most commonly reported and is related to rapid weight loss and deficiencies of iron, zinc and other micronutrients. 28 In the present study, the prevalence of hair loss was 59.5%, a rate which is in line with that reported by other researchers (40-60%); however, Goldenshluger et al observed a greater frequency of hair loss in MGB patients compared to those who underwent SG, while the opposite was true in the present study. 29 This may be related to the higher number of SG patients included in the current study and the fact that 55.3% had undergone the surgery between 1-2 years previously, a time when weight loss is commonly rapid in bariatric surgery patients.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed those females with a more severe hair loss after BS had lower values of zinc and iron, demanding for substitution. And there is a second type of temporary alopecia seen shortly after BC caused by protein deficiency …”
Section: Skin Diseases That Developed After Bariatric Surgerymentioning
confidence: 89%
“…Iron plays a critical role in the body, and this sheds light into the signs and symptoms that manifest when an individual is iron deficient. The clinical consequences of iron deficiency in bariatric surgery patients have been shown to negatively impact quality of life (13) and include general fatigue, weakness, cold intolerance, anemia, hair loss, pica, and cognitive impairments in concentration, attention and memory (14)(15)(16)(17). Because of issues such as a lack of monitoring and screening, reduced dietary intake of bioavailable iron, poor compliance to prophylactic iron supplementation, and poor response to treatment, bariatric surgery patients who develop iron deficiency often remain undiagnosed and untreated (1).…”
Section: Introductionmentioning
confidence: 99%